2-DIMENSIONAL ANIMATION DESIGN AS A HANPAINTED GOODS LIPCRAFT PROMOTION MEDIA - Mufida, Mey Imaniar (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
The aim of this project is to produce 2-dimensional animation as a promotional medium for Lipcraft Handpainted Goods. 2-dimensional animation was chosen to promote because using animation can be more attractive than static ads. This 2-dimensional animation design method goes through several stages, namely 1) the pre-production stage, 2) the production stage, 3) the post-production stage. This 2-dimensional animation design is informative, forming or creating awareness about existing Lipcraft Handpainted Goods products to the audience. This animation as a whole uses a cartoony style by highlighting the uniqueness of the Lipcraft Handpainted Goods products according to the USP, namely the product colors that show a feminine and cheerful impression. This 2-dimensional animation is published using social media Instagram and Youtube. The results of promotions through Instagram and Youtube get good insights.